Pemberian Nafkah Iddah Cerai Gugat Menurut Mazhab Syafi’i (Analisis Terhadap Putusan Mahkamah Agung No. 137/K/Ag/2007) - Ritonga, Zulkifli (Jurnal Landraad, 2022)
In the decision of the divorce case, the judge in the Religious Court requires a husband to pay the 'iddah of his ex-wife. As for the case for divorce (khulu ') in the Shafi'i school, it does not provide iddah for ex-wife. A wife who demands a divorce from her husband can abort her rights in the future, such as the right to a living during the 'iddah period and a mut'ah income. However, in the divorce decision at the Supreme Court regarding the divorce case, the judge gave a decision by granting the divorce lawsuit by charging the 'iddah cost of living to the husband. A lawsuit (khulu') is a divorce that occurs at the request of the wife by giving a ransom or 'iwadl to and with the approval of her husband. In this study, the subject of discussion is how the wife's 'iddah' livelihood rights after divorcing her husband according to the Syafi'i school? 137/K/AG/2007?, and Is the judge's consideration allowing the wife as the plaintiff to get the 'iddah maintenance right from her husband after the divorce? This research is the result of library research which is descriptive and analytical. The results of the research obtained are firstly, according to the Syafi'i school, the 'iddah income is not given to the ex-wife who divorced ba'in such as divorce (khulu') which is also categorized as talak ba'in sughra, secondly. 137/K/AG/2007 concerning the provision of a living 'iddah divorce, the panel of judges continues to provide a living 'iddah to the wife because the wife is not proven to have committed nusyuz, the three Supreme Court Judges' considerations regarding the 'iddah divorce claim are based on Article 41 letter (c) of the Law -Law No.1 of 1974 Jo, and Article 149 of the Compilation of Islamic Law.